2016
DOI: 10.1111/gcb.13303
|View full text |Cite
|
Sign up to set email alerts
|

High emissions of greenhouse gases from grasslands on peat and other organic soils

Abstract: Drainage has turned peatlands from a carbon sink into one of the world's largest greenhouse gas (GHG) sources from cultivated soils. We analyzed a unique data set (12 peatlands, 48 sites and 122 annual budgets) of mainly unpublished GHG emissions from grasslands on bog and fen peat as well as other soils rich in soil organic carbon (SOC) in Germany. Emissions and environmental variables were measured with identical methods. Site-averaged GHG budgets were surprisingly variable (29.2 ± 17.4 t CO -eq. ha yr ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
166
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 186 publications
(185 citation statements)
references
References 53 publications
17
166
0
2
Order By: Relevance
“…With rates of 6.5-9.4 t C ha −1 a −1 net CO 2 fluxes from organic soils now used as croplands were on average found to be higher than from organic soils under grassland, which were estimated to vary between 1.8 and 7.3 t C ha −1 a −1 (IPCC, 2014). However, recent studies reported emission rates of 7.6 ± 2.0 t C ha −1 a −1 on organic soils managed as grassland in Germany and thus much higher rates than previously found for this type of land use (Tiemeyer et al, 2016). Drained organic soils under forest can act as both net sinks or sources of atmospheric CO 2 (Cannell et al, 1993;Minkkinen and Laine, 1998;Minkkinen et al, 1999;Wüst-Galley et al, 2016), although they are in general considered to represent a source with average net CO 2 emissions of 2.0-3.3 t C ha −1 a −1 in the temperate zone (IPCC, 2014).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…With rates of 6.5-9.4 t C ha −1 a −1 net CO 2 fluxes from organic soils now used as croplands were on average found to be higher than from organic soils under grassland, which were estimated to vary between 1.8 and 7.3 t C ha −1 a −1 (IPCC, 2014). However, recent studies reported emission rates of 7.6 ± 2.0 t C ha −1 a −1 on organic soils managed as grassland in Germany and thus much higher rates than previously found for this type of land use (Tiemeyer et al, 2016). Drained organic soils under forest can act as both net sinks or sources of atmospheric CO 2 (Cannell et al, 1993;Minkkinen and Laine, 1998;Minkkinen et al, 1999;Wüst-Galley et al, 2016), although they are in general considered to represent a source with average net CO 2 emissions of 2.0-3.3 t C ha −1 a −1 in the temperate zone (IPCC, 2014).…”
Section: Introductionmentioning
confidence: 60%
“…Although they cover only 3 % of the earth's terrestrial surface (Tubiello et al, 2016), they store up to 30 % of the global soil organic carbon (SOC) pool (Parish et al, 2008). In Europe, more than 50 % of the former peatland area has been degraded by peat mining and conversion of land use, including drainage, to improve their suitability for agriculture or forestry (Joosten, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation of NEE by the choice of gap filling is in the range of recently reported uncertainties of discontinuous manual chamber data (Moffat et al, submitted). Interestingly, this variation is also in the same order of magnitude as the uncertainty reported with IPCC emission factors from organic soils ( Blain et al, ; Drösler et al, ) and other aggregated data sets and meta‐analyses of terrestrial C sources and sinks ( Wilson et al, ; Tiemeyer et al, ). Although very speculative, we propose that the S/C/I approach is likely closer to the true NEE of our system because studies using different methodologies (chamber measurements, long‐term crop records/soil sampling, and eddy covariance measurements) from agro‐ecosystems with forage crops ( e.g ., ryegrass and lucerne) generally estimate an NEE in the range of –100 to –400 g C m −2 ( Byrne et al, ; Bolinder et al, ; Gilmanov et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…() and Tiemeyer at al. () for permanent grasslands on fen soils in Denmark and Germany, respectively, obtained by a similar approach. NEE budgets for site UG were smaller compared to site GW, which confirms the general assumption for rewetted peatlands ( Augustin and Joosten , ).…”
Section: Discussionmentioning
confidence: 98%